Pruning, Harvesting and Maintenance of Florida-Friendly Edible Landscapes - Rachel Gutner; Tina McIntyre; Tiare Silvasy; Hamutahl Cohen; Esen Momol (EDIS)
Maintaining an edible landscape using the nine Florida-Friendly Landscaping™ (FFL) principles provides a practical approach to food production in the home environment. Integrating pest management strategies, addressing nutrient deficiencies, proper pruning techniques, timely harvesting, and mulching are all practices that contribute to having a healthy edible landscape. The audience for this new 6-page publication of the UF/IFAS Environmental Horticulture Department is Floridian homeowners attempting to grow edibles, such as vegetables, fruits and herbs. Written by Rachel Gutner, Tina McIntyre, Tiare Silvasy, Hamutahl Cohen, and Esen Momol. https://edis.ifas.ufl.edu/ep622